Galactic Model Parameters and Spatial Density of Cataclysmic Variables in the Gaia Era: New Constraints on Population Models - Remziye Canbay; Selçuk Bilir; Aykut Özdönmez; Tansel Ak (The Astronomical Journal, 2023)
The spatial distribution, Galactic model parameters, and luminosity function of cataclysmic variables (CVs) are established using reestimated trigonometric parallaxes from Gaia DR3. The data sample of 1587 CVs in this study is claimed to be suitable for Galactic model parameter estimation as the distances are based on trigonometric parallaxes, and the Gaia DR3 photometric completeness limits were taken into account when the sample was created. According to the analysis, the scale height of all CVs increases from 248 ± 2 to 430 ± 4 pc toward shorter periods near the lower limit of the period gap and suddenly drops to 300 ± 2 pc for the shortest orbital period CVs. The exponential scale heights of all CVs and the magnetic systems are found to be 375 ± 2 and 281 ± 3 pc, respectively, considerably larger than those suggested in previous observational studies. The local spatial density of all CVs and the magnetic systems in the sample are ${6.8}_{-1.1}^{+1.3}× $ 10 ^−6 and ${2.1}_{-0.4}^{+0.5}× {10}^{-6}$ pc ^−3 , respectively. Our measurements strengthen the 1–2 order of magnitude discrepancy between the CV spatial densities predicted by population synthesis models and observations. It is likely that this discrepancy is due to objects undetected by CV surveys, such as systems with very low $\dot{M}$ and ones in the period gap. A comparison of the luminosity function of white dwarfs with the luminosity function of all CVs in this study show that 500 times the luminosity function of CVs fits very well to the luminosity function of white dwarfs. We conclude that the estimations and data sample in this study can be confidently used for further analyses of CVs.